Teacher Scaffolding of Social and Intellectual Collaboration in Small Groups: A Comparative Case Study - Kraatz, Elizabeth; Nagpal, Manisha; Lin, Tzu-Jung; Hsieh, Ming-Yi; Ha, Seung Yon; Kim, Saetbyul; Shin, Sangin (Frontiers in Psychology, 2020)
This comparative case study features two small groups of students engaging in collaborative dialogue about social issues. The two groups were compared across three major components of the small groups system: social dynamics, intellectual collaboration, and teacher scaffolding. Our goal was to holistically analyze these small group processes to understand why some small groups were highly successful while others were not, even within the same intervention and with the same teacher. Results show that teacher scaffolding and existing student processes served to amplify one another reciprocally. The teacher heightened productive social norms when they were present, which then served to encourage productive intellectual collaboration. However, when productive group norms were not present, the teacher took increasing control over the group, which further hampered productive social and academic interactions.